2014
DOI: 10.2478/pjct-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Generation and Disposal of Municipal Solid Wastes in Selected Household in Rural Areas in the South-Western Poland

Abstract: Pilot study of the composition of wastes was carried out in 15 rural family households engaged in agricultural activity. In the study group the average resident of rural areas generates about 166 kg of municipal wastes annually. The conducted studies showed that the composition of municipal wastes coming from rural households changes seasonally. During the periods of summer and autumn, the quantity of bio-wastes increased distinctly. The average mass of wastes transferred to the companies engaged in the collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Uncontrolled incineration and unauthorized landfilling remain major problems as the worst solutions for plastic waste. Strzelczyk [272] has found that more than 80% of farmers burn their waste (including plastic) in household furnaces, resulting in significant air pollution. The total number of landfills in rural Poland is 318 [271].…”
Section: Balkan and Eastern Europementioning
confidence: 99%
“…Uncontrolled incineration and unauthorized landfilling remain major problems as the worst solutions for plastic waste. Strzelczyk [272] has found that more than 80% of farmers burn their waste (including plastic) in household furnaces, resulting in significant air pollution. The total number of landfills in rural Poland is 318 [271].…”
Section: Balkan and Eastern Europementioning
confidence: 99%